Pengaruh Debt to Equity Ratio (DER) dan Current Ratio (CR) Terhadap Harga Saham Pada PT Indo Tambangraya Megah Tbk Periode 2014-2024 - J, Junia; Febriana, Hadijah (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to determine the effect of Debt to Equity Ratio (DER) and Current Ratio (CR) on Share Price in PT Indo Tambangraya Megah Tbk for the 2014-2024 Period. The population used in this study is the financial statements of PT Indo Tambangraya Megah Tbk for 2014-2024. The sample used in this study is a report on financial position and closing stock price. The data analysis methods used in this study are descriptive statistical analysis, classical assumption tests which include normality tests, multicollinearity tests, heteroscedasticity tests and autocorrelation tests, multiple linear regression analysis, hypothesis testing including statistical tests t and f tests, and determination coefficients. The results show that the Debt to Equity Ratio (DER) does not have a significant effect on the Stock Price, it is based on a calculation tvalue that is smaller than the ttable (1.665 2.262) with a significance level of 0.134 greater than 0.05 (0.134 0.05). The results show that the Current Ratio (CR) has a significant effect on the Stock Price, this is based on the calculated tvalue greater than the ttable (2.836 2.262) with a significance level of 0.022 smaller than 0.05 (0.022 0.05). Simultaneously, Debt to Equity Ratio (DER) and Current Ratio (CR) have a significant effect on the Stock Price, this is obtained from the value of Fcalculated to be greater than the Ftable (5.174 4.459) and the significance level is 0.036 smaller than 0.05 (0.036 0.05).